ANALYSIS OF WASTE BANK MANAGEMENT MODEL AROUND LAKE TONDANO TOURISM OBJECT IN SUPPORTING SUSTAINABLE TOURISM DEVELOPMENT - Shirly Sussane Lumeno; Felly Ferol Warouw; Djubir Kembuan; Ricky Ratu (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2022)
Unmanaged waste can cause various problems of environmental damage including threatening tourism development. The current waste problem is quite worrying because it can have a direct impact on humans, such as the entry of plastic elements into the human body through fish or food exposed to microplastics. Aim: The waste bank around Lake Tondano tourism object was studied qualitatively with the aim of describing the waste bank management mechanism to be used as a model for developing a waste bank to support sustainable tourism development. Methodogy and Results: The research data was obtained through field research through observations and interviews with waste banks around the Tondano lake tourist attraction, in this case the Mapalus waste bank located in Papakelan Village. Conclusion, significance, and impact study: The results show that the current form of waste bank management on the shores of Lake Tondano is a waste bank that is purely managed by the community. The form of management is to collect waste from the community by first going through a sorting process. After sorting, organic waste is used as fertilizer and inorganic waste is made into valuable products and can be used as souvenirs for tourists. The waste bank program can reduce the increase in waste directly from the source. In addition, the waste bank can produce new products and provide benefits to the community. The waste bank is also a solution in the context of developing tourism on the coast of Lake Tondano.